1996
DOI: 10.1044/jshr.3904.881
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Repair by Individuals With Dementia of the Alzheimer's Type

Abstract: Conversational repair was examined in videotaped samples of spontaneous mealtime talk of 6 normal elderly adults, 5 subjects with early stage dementia of the Alzheimer's type (EDAT) and 5 subjects with middle stage DAT (MDAT) with a family member who acted as a conversational partner. The overall percentage of utterances involved in communication breakdown and repair and the specific proportions of utterances related to conversation problems, signals identifying problems, and repairs, were evaluated. Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
11

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 40 publications
4
68
0
11
Order By: Relevance
“…It is also worthy of note, that PWD initiated repair, something that has been described as problematic in previous research (Orange et al, 1996). In conversations that involve PWD repairs are often elaborated and involve many turns (Orange et al, 1996). In many cases attempts to self-repair by the person with dementia may require quite an extended number of turns involving the need for repair support by the other person.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also worthy of note, that PWD initiated repair, something that has been described as problematic in previous research (Orange et al, 1996). In conversations that involve PWD repairs are often elaborated and involve many turns (Orange et al, 1996). In many cases attempts to self-repair by the person with dementia may require quite an extended number of turns involving the need for repair support by the other person.…”
Section: Discussionmentioning
confidence: 99%
“…The repair trajectories demonstrated that for both groups the interactional repair was a collaborative process, where both spouses were actively involved. It is also worthy of note, that PWD initiated repair, something that has been described as problematic in previous research (Orange et al, 1996). In conversations that involve PWD repairs are often elaborated and involve many turns (Orange et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Real-World Example: Trouble-Source Repair and Topic Maintenance in Dementia of the Alzheimer's Type (DAT) Background Individuals with DAT have problems participating in meaningful conversations, and these problems worsen as the disease progresses (Guendouzi & Müller, 2002;Orange & Colton-Hudson, 1998;Orange, Lubinski, & Higginbotham, 1996;Orange, Van Gennep, Miller, & Johnson, 1998;Watson, Chenery, & Carter, 1999). This deterioration in conversational ability creates more conversational breakdowns, which, in turn, require caregivers to spend more time and effort repairing these breakdowns (Orange et al, 1996.…”
Section: Dicamentioning
confidence: 99%